Quantification of global and national nitrogen budgets for crop production - Zhang, Xin; Zou, Tan; Lassaletta, Luis; Mueller, Nathaniel D; Tubiello, Francesco N; Lisk, Matthew D; Lu, Chaoqun; Conant, Richard T; Dorich, Christopher D; Gerber, James; Tian, Hanqin; Bruulsema, Tom; et al. (Nature food, 2021)
Input-output estimates of nitrogen on cropland are essential for improving nitrogen management and better understanding the global nitrogen cycle. Here, we compare 13 nitrogen budget datasets covering 115 countries and regions over 1961-2015. Although most datasets showed similar spatiotemporal patterns, some annual estimates varied widely among them, resulting in large ranges and uncertainty. In 2010, global medians (in TgN yr ) and associated minimum-maximum ranges were 73 (64-84) for global harvested crop nitrogen; 161 (139-192) for total nitrogen inputs; 86 (68-97) for nitrogen surplus; and 46% (40-53%) for nitrogen use efficiency. Some of the most uncertain nitrogen budget terms by country showed ranges as large as their medians, revealing areas for improvement. A benchmark nitrogen budget dataset, derived from central tendencies of the original datasets, can be used in model comparisons and inform sustainable nitrogen management in food systems.